1935
DOI: 10.1097/00000658-193501000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Osteochondroma of Dural Origin

Abstract: THiV following case is recorded partly because of its rarity, and partly to indicate its origin from the meningeal fibroblasts. In so doing some semblance of order has been given to what might otherwise appear to be an encapsulated tumor wholly unrelated to the other encapsulated tumors of the cerebrum. At the same time it has been rescued from the large group of tumors of unexplained origin.Case Report.-Motor and sensory jacksonian convulsions involving the right leg and trunk for three years in a man of fort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

1950
1950
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…Theoretically, a chondrosarcoma should originate from the mesenchymal tissues, like cartilage, therefore, those arising from the skull base are quite natural. Intracranial chondrosarcomas are also thought to arise from the mesenchymal elements of the central nervous system, such as, the primitive multipotential mesenchymal cells or their mature descendents (fibroblasts, meningeal cells, and pial cells) located within the leptomeninges, the pia-arachnoid surrounding blood vessels or in the vessel walls, the stroma of the choroid plexus and aberrant embryonal cartilagenous rests (4,7,(9)(10)(11)(12)(13)(14)(15)(16). In the case of primary intraparenchymal chondrosarcoma, misplaced embryonal cartilagenous rests or primitive multipotential mesenchymal cells in leptomeningeal sheaths around vessels or the vessel walls have been suggested to be origins without definitive evidence (3,5,7,8,10,(17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, a chondrosarcoma should originate from the mesenchymal tissues, like cartilage, therefore, those arising from the skull base are quite natural. Intracranial chondrosarcomas are also thought to arise from the mesenchymal elements of the central nervous system, such as, the primitive multipotential mesenchymal cells or their mature descendents (fibroblasts, meningeal cells, and pial cells) located within the leptomeninges, the pia-arachnoid surrounding blood vessels or in the vessel walls, the stroma of the choroid plexus and aberrant embryonal cartilagenous rests (4,7,(9)(10)(11)(12)(13)(14)(15)(16). In the case of primary intraparenchymal chondrosarcoma, misplaced embryonal cartilagenous rests or primitive multipotential mesenchymal cells in leptomeningeal sheaths around vessels or the vessel walls have been suggested to be origins without definitive evidence (3,5,7,8,10,(17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Primary intracranial extraosseous chondrosarcoma is rare and most are attached to the dura, the presumed site of origin of these tumors (4)(5)(6)(7). However, seven cases of primary intracranial chondrosarcomas unrelated to the cranium or the meninges have been reported and all of these tumors were histologically typed as mesenchymal variants (3,5).…”
Section: Introductionmentioning
confidence: 99%
“…Skull radiography (1B), CT and M RI ( (1881) (quoted by Alpers) w as the ® rst to report on a m eningeal chondrom a. 8 In 1933, Chorobski et al culled 25 cases of cranial cartilaginous tum ours from the world literature and added one case of their own; only ® ve of these cases involved the skull base. 9 W hereas Siqueira and Bucy wrote in 1966: w hen in the skull' chondrom as`are m ore com m on in the vault than in the base' , 19 Berkm en, in 1968, found that 63% of 113 cartilaginous tum ours reported in the world literature occurred at the skull base.…”
Section: Ase Reportmentioning
confidence: 99%
“…
Primary intracranial cartilaginous neoplasms which do not arise from bones of the skull are extremely rare (Alpers, 1935;Chorobski, Jarzymski, and Ferens, 1939;Dahlin and Henderson, 1962;Flyger, Freidenfeldt, and Orell, 1963;Siris and Angrist, 1942). We report herein two such tumours; one benign and the other malignant.

CASE 1: CHONDROMA During the seventh month of pregnancy L.W., a 32-yearold white woman, began to exp-rience fainting spells of 15 minutes' duration followed by increasingly severe speech difficulty and weakness in the right arm.

…”
mentioning
confidence: 99%
“…These tumours have originated in various bones, the meninges, and the temporal muscle, but involve the long bones less frequently than the usual chondrosarcoma. Dahlin and Henderson (1962) (Chorobski et al, 1939;Money, 1943;David and Constans, 1957), metaplasia from fibroblasts (Brutt, 1931;Froment et al, 1932;Van Wagenen, 1934;Alpers, 1935;Baker and Adams, 1937;Cushing and Eisenhardt (1938) (Maximow and Bloom, 1942;Maximow, 1952 Experimentally ectopic cartilage has been pro-duced by Stephenson (1952) by means of injection of alcoholic and other extracts of cartilage and bone into rabbits and by transplanting epithelium into the rectus muscles of dogs and rats. Grobstein and Parker (1954) produced cartilage in vitro in the mouse somite mesoderm by adding embryonic spinal cord.…”
mentioning
confidence: 99%